The judicial review of legislation in the peruvian Constitution of 1993 - Hakansson, Carlos (Derecho Público Iberoamericano, 2019)
Since 1979, the Peruvian Constitutional Law has a double system to control legislation. First of all, any judge can declare the unconstitutionality about any norm against the constitution supremacy, and, the second way, with a separate and independent Constitutional Court, can leave without effects any norm or treaty against it. Both systems make possible the judicial review, with no crossings because the last decision is from the Constitutional Court. This paper wants to explore the origin of this special kind of constitutional control in the region.